KAJIAN KELIMPAHAN IKAN KARANG PADA EKOSISTEM TERUMBU KARANG UNTUK ZONA INTI DI KABUPATEN BELITUNG - Prihadi, Donny J.; Sriati, Sriati; Prasetyo, Dany Arisandi (Coastal and Marine Resources Research Center, Raja Ali Haji Maritime University, Tanjungpinang, Indonesia, 2018)
The research was carried out in March 2014 in Belitung District aims to study the abundance of reef fish, and determine the suitability of the area on coral reef community. This research using the method of survey on six stations observations determined based on resource utilization activities around the station, primarily tourism activities. Analysis of the conformity analysis is used to determine the core zone of the area of coral reefs. Parameters in determining the suitability of the core zone includes the quality of the waters, index of ecological fish, the percentage coverage of the coral, the reef ecological index, and the existence of important economically as well as biodiversity and rare species. The results showed Underwater Visual Census (UVC) found an abundance of reef fish ranges between 61 â 448 individuals and 33 species in the entire station. Found 12 family Ambassidae, Blenniidae, i.e., Chaetodontidae, Gobiidae, Haemulidae, Labridae, Lutjanidae, Mullidae, Pomacanthidae, Pomacentridae, Scaridae, and Siganidae, conditions of coral reefs in the waters of the Belitung district included in the category are up to. The percentage of coverage of the coral reefs in the observation stations ranged between 37.37%-81.77%. The corresponding observation stations for the core zone is located on Pulau Begador, Batu Berlayar and Batu Garuda, while a very appropriate observation stations for the core zone is located on Pulau Lengkuas, Pulau Babi, and Batu Malang Penyu.